2017
DOI: 10.1534/g3.116.038711
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Gene Expression Balance Among Homeologs of Natural Polyploids

Abstract: Polyploidy is a major evolutionary process in eukaryotes, yet the expression balance of homeologs in natural polyploids is largely unknown. To study this expression balance, the expression patterns of 2180 structurally well-characterized genes of wheat were studied, of which 813 had the expected three copies and 375 had less than three. Copy numbers of the remaining 992 ranged from 4 to 14, including homeologs, orthologs, and paralogs. Of the genes with three structural copies corresponding to homeologs, 55% e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 76 publications
1
22
0
1
Order By: Relevance
“…5A-B) and subcellular localization (Table S2). SV between homeologs might result in different gene regulation of gene expression and consequently lead to novel functions 33 . Diverse gene expression patterns among FaMLO genes across different tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5A-B) and subcellular localization (Table S2). SV between homeologs might result in different gene regulation of gene expression and consequently lead to novel functions 33 . Diverse gene expression patterns among FaMLO genes across different tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Wagner (2005) suggested that there are two potential drivers of less-than-additive (Eshed and Zamir 1996) or synergistic It may be that there are few differences in protein function or expression across the three subgenomes, although this seems unlikely given mounting evidence that homeologous copies are differentially expressed in time, tissue and environment (Adams et al 2003;Liu and Adams 2007;Chaudhary et al 2009;Liu et al 2011Liu et al , 2015Pfeifer et al 2014;Zhang et al 2016;Mutti et al 2017). We were unable to assign homeologous pairs to all genes within the genome, suggesting that many of these potential sites for interacting loci were lost during polyploidization.…”
Section: Further Considerationsmentioning
confidence: 99%
“…It may be that there are few differences in protein function or expression across the three subgenomes, although this seems unlikely given mounting evidence that homeologous copies are differentially expressed in time, tissue and environment (Adams et al ., 2003; Liu and Adams, 2007; Liu et al ., 2011; Chaudhary et al ., 2009; Pfeifer et al ., 2014; Liu et al ., 2015; Zhang et al ., 2016; Mutti et al ., 2017). We were unable to assign homeologous pairs to all genes within the genome, suggesting that many of these potential sites for interacting loci were lost during polyploidization.…”
Section: Further Considerationsmentioning
confidence: 99%